1930
DOI: 10.1111/j.1540-4781.1930.tb00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Why Prognose in the Foreign Languages?

Abstract: Author's summary.— Let us not throw out students on the basis of prognosis tests, but rather reorganize our language courses to suit them to the average pupil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1931
1931
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In keeping with previous decades, learners were frequently described simply as 'students' or as members of a particular year or grade level. Beginning a conversation that would feature prominently in future decades, Kaulfers (1930) critiqued 'prognostic' selection practices, which were widespread and based on measures such as mother tongue proficiency, achievement in junior high school exploratory classes (e.g., Lindquist, 1930), IQ, and standardized tests of linguistic aptitude. Both Kaulfers (1930) and Warshaw (1931) questioned the validity of these measures and their role in excluding less prepared students from language study-whom Lindquist called "the linguistically unfit" (p. 289)-when questionable teaching practices were perhaps to blame for student course failure.…”
Section: Smentioning
confidence: 99%
See 2 more Smart Citations
“…In keeping with previous decades, learners were frequently described simply as 'students' or as members of a particular year or grade level. Beginning a conversation that would feature prominently in future decades, Kaulfers (1930) critiqued 'prognostic' selection practices, which were widespread and based on measures such as mother tongue proficiency, achievement in junior high school exploratory classes (e.g., Lindquist, 1930), IQ, and standardized tests of linguistic aptitude. Both Kaulfers (1930) and Warshaw (1931) questioned the validity of these measures and their role in excluding less prepared students from language study-whom Lindquist called "the linguistically unfit" (p. 289)-when questionable teaching practices were perhaps to blame for student course failure.…”
Section: Smentioning
confidence: 99%
“…Beginning a conversation that would feature prominently in future decades, Kaulfers (1930) critiqued 'prognostic' selection practices, which were widespread and based on measures such as mother tongue proficiency, achievement in junior high school exploratory classes (e.g., Lindquist, 1930), IQ, and standardized tests of linguistic aptitude. Both Kaulfers (1930) and Warshaw (1931) questioned the validity of these measures and their role in excluding less prepared students from language study-whom Lindquist called "the linguistically unfit" (p. 289)-when questionable teaching practices were perhaps to blame for student course failure. The use of assessments for course placement was also viewed with some distrust by practitioners in university language programs, like Sammartino (1935), who suggested that "the addition of a grain of salt" (p. 272) to assessment scores was necessary to adequately place students in appropriate classes.…”
Section: Smentioning
confidence: 99%
See 1 more Smart Citation
“…Another early and major theme in MLJ articles on testing was language learning aptitude. Kaulfers (1930) was the first to raise the prognosis question, as it was called at that time, in the MLJ. Effective prognosis was seen as a screening device needed to keep poor students out of language classes.…”
Section: Prognosis or Aptitude Testingmentioning
confidence: 99%